Sunday
March 26, 2017

Post a New Question

Posted by on .

How do i solve this problem?

2(x-3)-3(x+5)=3(x-2)-7

what are the steps to solving this equation? HELP!!!

Multply out the parentheses and then combine terms
First step:
2x - 6 -3x -15 = 3x -6 -7
-x -21 = 3x -13
Nox add x + 13 to both sides of the equation
-8 = 4x
One more step: Divide both sides of the equation by 4.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question